2014
DOI: 10.4067/s0718-27242014000200012
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of TQM in R & D Environments

Abstract: Research & development has been identified as a key element to achieve competitive advantage, particularly in contexts of change and especially for technology-based companies. Nowadays, organizations are aware that quality, and quality management as a consequence, represents an important strategic stimulus, thus assuming a fundamental role in the business strategies implementation. This article, aiming at outlining the practices that managers believe are critical for achieving quality management in applied res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 52 publications
0
20
0
1
Order By: Relevance
“…The participants were selected to represent the stakeholders and those who influence the observed events. As to the third step, the data are collected from empirical case studies conducted on industrial companies and reported in the literature [15,16]. Two key referenced papers on case studies that suit the specific focus of the present paper, that are related to each other, that are highly cited and that are authored by leading research authorities, are adopted and utilized in the present paper:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were selected to represent the stakeholders and those who influence the observed events. As to the third step, the data are collected from empirical case studies conducted on industrial companies and reported in the literature [15,16]. Two key referenced papers on case studies that suit the specific focus of the present paper, that are related to each other, that are highly cited and that are authored by leading research authorities, are adopted and utilized in the present paper:…”
Section: Methodsmentioning
confidence: 99%
“…(II) On the remaining practices in R&D-based companies [16]. This study focused on all practices in a smaller sample of R&D-based companies and adopted the validated questionnaire on TQM practices in the sample of R&D-based companies used by [15].…”
Section: Methodsmentioning
confidence: 99%
“…Studying the practice of competitive struggle in the modern economy shows that innovation, the development of new products and services involves extensive and intensive activities in the field of knowledge. "Research & development has been identified as a key element to achieve competitive advantage, particularly in contexts of change and especially for technology-based companies" (Bigliardi & Galati, 2014;p.157). The transformation of knowledge provides value to its customers and helps to achieve a competitive position in the market (Griffith et al, 2006).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…Another unique feature of total quality management is that each group of personnel have a range of qualifications and training which is then harnessed together to form a strong team for the execution of the quality management system. Suffice it to say that human resource is the foundation on which total quality management is built [11,12].…”
Section: Human Resources In Total Quality Management 31 the Importanmentioning
confidence: 99%